C-reactive protein flare: a promising prognostic predictor for patients with hepatocellular carcinoma treated with TACE combined with lenvatinib and immune checkpoint inhibitors - Li, Xinge; Chang, Xu; Wu, Huiyong; Han, Jianjun; Wu, ChunXue (Frontiers in Immunology, 2025)
PurposeTo assess the prognostic value of C-reactive protein (CRP) kinetics in patients with hepatocellular carcinoma (HCC) treated with transarterial chemoembolisation (TACE) combined with lenvatinib (LEN) and immune checkpoint inhibitors (ICIs).MethodsThis study retrospectively analysed CRP kinetics for 143 HCC patients treated with TACE–LEN–ICIs from December 2020 to February 2024. Initially, patients were classified into three groups based on early CRP kinetics: (i) CRP flare-responders, whose levels increased to more than double the baseline value within 1 month of the initial TACE–LEN–ICIs regime followed by a decrease to below baseline within 3 months; (ii) CRP responders, where levels decreased by at least 30% from baseline within 3 months without an initial flare; and (iii) CRP non-responders (comprising all remaining patients). Overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and disease control rate (DCR) were calculated as oncological outcomes. A correlation between these outcomes and CRP kinetics was examined in this study.ResultsThe CRP flare-responder, CRP responder, and CRP non-responder groups included 19 (13.3%), 60 (42.0%), and 64 (44.7%) patients, respectively, exhibiting ORRs of 78.9%, 78.4% and 48.4% (p = 0.001) and DCRs of 94.8%, 96.7% and 78.1% (p = 0.004). Median PFS for the three respective groups was 40.3, 11.4, and 5.5 months (p < 0.001), while median OS values were not reached, 18.9 and 9.9 months (p < 0.001). Moreover, CRP responder and CRP flare-responder status were independent risk factors for OS (p < 0.001) and PFS (p < 0.001).ConclusionCRP kinetics may have predictive value for prognosis in HCC patients undergoing TACE–LEN–ICIs.